122k views
5 votes
Simplify: -10(x – 7) – 3x

User Xonar
by
6.5k points

2 Answers

2 votes

Answer:

-13x+70

Explanation:

Isolate x on one side of the equation.

DISTRIBUTIVE PROPERTY

A(B+C)=AB+AC

A(B-C)=AB-AC

-10(x-7) (First, expand by using with distributive property.)

-10*x=-10x

10*7=70

-10x+70

-10x+70-3x

-10x+70-3x (Solve & add.)

10+3=13

-13x+70

Therefore, the final answer is -13x+70.

User Redanimalwar
by
5.4k points
4 votes

Answer:

-13x+70

Explanation:

expand the bracket

simplify like terms

User Jasha
by
5.8k points